1999
DOI: 10.1073/pnas.96.9.5049
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA specifically disrupts gene expression during planarian regeneration

Abstract: Metazoan regeneration is one of the least understood fundamental problems of biology. The lack of progress in understanding this phenomenon at the molecular level has been due to the poor regenerative abilities of the genetic organisms used for developmental studies, as well as the difficulties encountered with molecular and genetic manipulations of the commonly studied vertebrate models (the urodele amphibians). Here, we demonstrate that introduction of double-stranded RNA selectively abrogates gene function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
262
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(268 citation statements)
references
References 24 publications
4
262
0
2
Order By: Relevance
“…RNA interference (RNAi) is a recently described phenomenon whereby gene-specific double-stranded RNA (dsRNA) induces degradation of target mRNA with consequent sequence-specific inhibition of gene expression+ Originally reported in Caenorhabditis elegans , RNAi has been described in organisms as diverse as Trypanosoma brucei (Ngo et al+, 1998), Planaria (Sanchez Alvarado & Newmark, 1999), Hydra (Lohmann et al+, 1999), and Drosophila (Misquitta & Paterson, 1999)+ In plants, a variety of RNA-mediated silencing mechanisms are referred to as posttranscriptional gene silencing (PTGS) (Wassenegger & Pelissier, 1998), whereas PTGS in the fungus Neurospora has been termed "quelling" (Cogoni et al+, 1996)+ The mechanism of RNAi is at present poorly understood+ Given the gene-specific nature of RNAi, dsRNA needs to interact specifically with its target mRNA+ Whether there exist cellular factors that enhance dsRNA-mRNA recognition and how and in which compartment mRNA degradation is initiated are among the open questions+ Recently, several genes involved in the RNAi pathway have been identified in C. elegans, namely the rde (Tabara et al+, 1999) genes and mut-7 (Ketting et al+, 1999)+ rde-1 is part of a multigene family with homologs in plants, animals, and in fission yeast, but its precise function is not known+ The mut-7 gene bears the signature motif of RNase D and might represent one of the ribonucleases involved in mRNA degradation+ Interestingly, some rde as well as mut-7 mutant animals have enhanced levels of transposon mobilization, suggesting that in C. elegans one of the functions of RNAi might be to protect the organism from transposition damage by mobile elements+ In quellingdeficient Neurospora cells, the mutant gene qde-1 has similarity to RNA-dependent RNA polymerase of plants, suggesting that RNA synthesis by this enzyme might contribute to the PTGS response in this organism (Cogoni & Macino, 1999a)+ Furthermore, recently another gene qde-3, a member of the RecQ DNA helicase family, has been shown to be required for the activation and maintenance of gene silencing in Neurospora crassa (Cogoni & Macino, 1999b)+ To induce RNAi, dsRNA is delivered into cells using various methods depending on the organism's biology: the most common one being microinjection of synthetic dsRNA+ In C. elegans it is also possible to soak worms in dsRNA solutions (Tabara et al+, 1998), and by an unknown mechanism, the dsRNA makes its way into cells+ In trypanosomes we have shown that transient expression of tubulin dsRNA from plasmid constructs or electroporation of synthetic tubulin dsRNA causes degradation of tubulin mRNA (Ngo et al+, 1998)+ This resulted in a transient block of tubulin synthesis with the arrest of cytokinesis and consequent accumulation of cells with two nuclei, two kinetoplasts (mitochondrial genome), two basal bodies, and two flagella+ After tubulin synthesis resumed, trypanosomes progressed through the cell cycle one more time, duplicated basal bodies and flagella, and carried out nuclear and kinetoplast division+ At this point long slender trypanosomes became large almost spherical cells, which we na...…”
Section: Introductionmentioning
confidence: 99%
“…RNA interference (RNAi) is a recently described phenomenon whereby gene-specific double-stranded RNA (dsRNA) induces degradation of target mRNA with consequent sequence-specific inhibition of gene expression+ Originally reported in Caenorhabditis elegans , RNAi has been described in organisms as diverse as Trypanosoma brucei (Ngo et al+, 1998), Planaria (Sanchez Alvarado & Newmark, 1999), Hydra (Lohmann et al+, 1999), and Drosophila (Misquitta & Paterson, 1999)+ In plants, a variety of RNA-mediated silencing mechanisms are referred to as posttranscriptional gene silencing (PTGS) (Wassenegger & Pelissier, 1998), whereas PTGS in the fungus Neurospora has been termed "quelling" (Cogoni et al+, 1996)+ The mechanism of RNAi is at present poorly understood+ Given the gene-specific nature of RNAi, dsRNA needs to interact specifically with its target mRNA+ Whether there exist cellular factors that enhance dsRNA-mRNA recognition and how and in which compartment mRNA degradation is initiated are among the open questions+ Recently, several genes involved in the RNAi pathway have been identified in C. elegans, namely the rde (Tabara et al+, 1999) genes and mut-7 (Ketting et al+, 1999)+ rde-1 is part of a multigene family with homologs in plants, animals, and in fission yeast, but its precise function is not known+ The mut-7 gene bears the signature motif of RNase D and might represent one of the ribonucleases involved in mRNA degradation+ Interestingly, some rde as well as mut-7 mutant animals have enhanced levels of transposon mobilization, suggesting that in C. elegans one of the functions of RNAi might be to protect the organism from transposition damage by mobile elements+ In quellingdeficient Neurospora cells, the mutant gene qde-1 has similarity to RNA-dependent RNA polymerase of plants, suggesting that RNA synthesis by this enzyme might contribute to the PTGS response in this organism (Cogoni & Macino, 1999a)+ Furthermore, recently another gene qde-3, a member of the RecQ DNA helicase family, has been shown to be required for the activation and maintenance of gene silencing in Neurospora crassa (Cogoni & Macino, 1999b)+ To induce RNAi, dsRNA is delivered into cells using various methods depending on the organism's biology: the most common one being microinjection of synthetic dsRNA+ In C. elegans it is also possible to soak worms in dsRNA solutions (Tabara et al+, 1998), and by an unknown mechanism, the dsRNA makes its way into cells+ In trypanosomes we have shown that transient expression of tubulin dsRNA from plasmid constructs or electroporation of synthetic tubulin dsRNA causes degradation of tubulin mRNA (Ngo et al+, 1998)+ This resulted in a transient block of tubulin synthesis with the arrest of cytokinesis and consequent accumulation of cells with two nuclei, two kinetoplasts (mitochondrial genome), two basal bodies, and two flagella+ After tubulin synthesis resumed, trypanosomes progressed through the cell cycle one more time, duplicated basal bodies and flagella, and carried out nuclear and kinetoplast division+ At this point long slender trypanosomes became large almost spherical cells, which we na...…”
Section: Introductionmentioning
confidence: 99%
“…Animals were fixed as previously described (Newmark et al, 2003;Sánchez Alvarado and Newmark, 1999). Following rehydration animals were blocked for 6 hours at room temperature (RT) in PBTxB (PBS+0.3% Triton X-100+0.25% BSA), then incubated overnight with 1:5000 VC-1 (kind gift of Dr K. Agata, RIKEN, Kobe, Japan), 1:133 anti-Synaptotagmin (kind gift of Dr K. Agata), 1:400 anti-acetylated tubulin .…”
Section: Antibody Stainingmentioning
confidence: 99%
“…How do wounded planarian tissues specify what to regenerate, and what rules govern the rearrangement of body coordinates? Recent technological developments (Newmark and Sánchez Alvarado, 2000;Newmark et al, 2003;Reddien et al, 2005a;Sánchez Alvarado and Newmark, 1999) make it now possible to begin to address these long-standing questions.…”
Section: Introductionmentioning
confidence: 99%
“…R NA interference (RNAi) is a cellular pathway that was first discovered in the nematode worm Caenorhabditis elegans, 1 but is present in many other organisms like the fruitfly Drosophila, 2 -4 insects, 5 protozoa, 6 planaria, 7 and hydra 8 and seems to represent an ancient pathway. 9 This phenomenon was given a variety of names like cosuppression, quelling, gene silencing, and RNAi, as various research groups had been seeing clues that cells have some novel way of shutting down or ''silencing'' genes.…”
mentioning
confidence: 99%